Span 60/Cholesterol Niosomal Formulation as a Suitable Vehicle for Gallic Acid Delivery with Potent In Vitro Antibacterial, Antimelanoma, and Anti-Tyrosinase Activity - Sara Zolghadri; Ali Ghanbari Asad; Fatemeh Farzi; Fatemeh Ghajarzadeh; Zeinab Habibi; Mahdie Rahban; Samaneh Zolghadri; Agata Stanek (MDPI AG, 2023)
Natural compounds such as gallic acid (GA) have attracted more attention in cosmetic and pharmaceutical skin care products. However, the low solubility and poor stability of GA have limited its application. This study aimed to synthesize and characterize the GA niosomal dispersion (GAN) and investigate the potential of an optimal formulation as a skin drug delivery system for GA. For this purpose, GAN formulations were synthesized using the thin layer evaporation method with different molar ratios of Tween 60/Span 60, along with a constant molar ratio of polyethylene glycol 4000 (PEG-4000) and cholesterol in a methanol and chloroform solvent (1:4 v/v). The physicochemical properties of nanosystems in terms of size, zeta potential, drug entrapment, drug release, morphology, and system-drug interaction were characterized using different methods. In addition, in vitro cytotoxicity, anti-tyrosinase activity, and antibacterial activity were evaluated by MTT assay, the spectrophotometric method, and micro-well dilution assay. All formulations revealed a size of 80-276 nm, polydispersity index (PDI) values below 0.35, and zeta potential values below-9.7 mV. F2 was selected as the optimal formulation due to its smaller size and high stability. The optimal formulation of GAN (F2) was as follows: a 1:1 molar ratio of Span 60 to cholesterol and 1.5 mM GA. The release of the F2 drug showed a biphasic pattern, which was fast in the first 12 h until 58% was released. Our results showed the high antibacterial activity of GAN against Escherichia coli and Pseudomonas aeruginosa. The MTT assay showed that GA encapsulation increased its effect on B6F10 cancer cells. The F2 formulation exhibited potent anti-tyrosinase activity and inhibited melanin synthesis. These findings suggest that it can be used in dermatological skin care products in the cosmetic and pharmaceutical industries due to its significant antibacterial, anti-melanoma, and anti-tyrosinase activity.